The mortality and direct medical costs of osteoporotic fractures among postmenopausal women in Taiwan. Issue 2 (February 2016) - Chang, C.-Y.; Tang, C.-H.; Chen, K.-C.; Huang, K.-C.; Huang, K.-C.
Abstract Summary This study estimated the fracture-related mortality and direct medical costs among postmenopausal women in Taiwan by fracture types and age groups by utilizing a nationwide population-based database. Results demonstrated that hip fractures constituted the most severe and expensive complication of osteoporosis across fracture sites. Introduction The aims of the study were to evaluate the risk of death and direct medical costs associated with osteoporotic fractures by fracture types and age groups among postmenopausal women in Taiwan. Methods This nationwide, population-based study was based on data from the National Health Insurance Research Database in Taiwan. Female patients aged 50 years and older in the fracture case cohort were matched in 1:1 ratio with randomly selected subjects in the reference control cohort by age, income-related insurance amount, urbanization level, and the Charlson comorbidity index. There were two main outcome measures of the study: age-differentiated mortality and direct medical costs in the first and subsequent years after osteoporotic fracture events among postmenopausal women. The bootstrap method by resampling with replacement was conducted to generate descriptive statistics of mortality and direct medical costs of the case and control cohorts. Student'st tests were then performed to compare mortality and costs between the two cohorts. Results A total of 155, 466 postmenopausal women in the database met the inclusion criteria for the fracture case cohort, including 22, 791 hip fractures, 72, 292 vertebral fractures, 15, 621 upper end humerus (closed) fractures, 36, 774 wrist fractures, and 7, 988 multiple fractures. Analytical results demonstrated that patients experiencing osteoporotic fractures were at considerable excess risk of death and incurred substantially higher treatment costs, notably for hip fractures. Furthermore, results also revealed that the risk of mortality increased with advancing age across the spectrum of fracture sites. Conclusions The present study confirmed an excess mortality and higher direct medical costs associated with osteoporotic fractures. Moreover, hip fractures constituted the most severe and expensive complication of osteoporosis among fracture types.